Improvement of laser ablation in situ micro-analysis to identify diagenetic alteration and measure strontium isotope ratios in fossil human teeth. (June 2016) - Willmes, M.; Kinsley, L.; Moncel, M.-H.; Armstrong, R.A.; Aubert, M.; Eggins, S.; Grün, R.
Abstract: Strontium isotope ratios measured in fossil human teeth are a powerful tool to investigate past mobility patterns. In order to apply this method, the sample needs to be investigated for possible diagenetic alteration and a least destructive analytical technique needs to be employed for the isotopic analysis. We tested the useability of U, Th, and Zn distribution maps to identify zones of diagenetic overprint in human teeth. Areas with elevated U concentrations in enamel were directly associated with diagenetic alterations in the Sr isotopic composition. Once suitable domains within the tooth are identified, strontium isotope ratios can be determined either with micro-drilling followed by TIMS analysis or in situ LA-MC-ICP-MS. Obtaining accurate 87 Sr/ 86 Sr isotope ratios from LA-MC-ICP-MS is complicated by the potential occurrence of a significant direct interference on mass 87 from a polyatomic compound. We found that this polyatomic compound is present in our analytical setup but is Ar rather than Ca based, as was previously suggested. The effect of this interference can be significantly reduced by tuning the instrument for reduced oxide levels. We applied this improved analytical protocol to a range of human and animal teeth and compared the results with micro-drilling strontium isotopic analysis using TIMS. Tuning for reduced oxide levels allowed the measurement of accurate strontium isotope ratios from human and animal tooth enamel and dentine, even at low Sr concentrations. The average offset between laser ablation and solution analysis using the improved analytical protocol is 38 ± 394 ppm (n = 21, 2σ). LA-MC-ICP-MS thus provides a powerful alternative to micro-drilling TIMS for the analysis of fossil human teeth. This method can be used to untangle diagenetic overprint from the intra-tooth isotopic variability, which results from genuine changes in 87 Sr/ 86 Sr isotope ratios related to changes in food source, and by extension mobility. Highlights: LA-ICP-MS can be used to identify zones of least diagenetic overprint in fossil teeth. The analytical interference on mass 87 is caused by an Ar based polyatomic compound. Tuning the instrument for reduced oxide levels significantly reduces the interference. Monitoring this interference is critical to obtain accurate 87 Sr/ 86 Sr isotope ratios.